Correlation Between Clinical and Radiological Outcomes After Matrix-Induced Autologous Chondrocyte Implantation in the Femoral Condyles. (August 2014) - Ebert, Jay R.; Smith, Anne; Fallon, Michael; Wood, David J.; Ackland, Timothy R.
Background: Matrix-induced autologous chondrocyte implantation (MACI) is an established technique for the repair of knee chondral defects, although the correlation between clinical and radiological outcomes after surgery is poorly understood. Purpose: To determine the correlation between clinical and radiological outcomes throughout the postoperative timeline to 5 years after MACI. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: This retrospective study was undertaken in 83 patients (53 male, 30 female) with complete clinical and radiological follow-up at 1, 2, and 5 years after MACI. The mean age of patients was 38.9 years (range, 13-62 years), with a mean body mass index (BMI) of 26.6 kg/m 2 (range, 16.8-34.8 kg/m 2 ), mean defect size of 3.3 cm 2 (range, 1-9 cm 2 ), and mean preoperative duration of symptoms of 9.2 years (range, 1-46 years). Patients indicated for MACI in this follow-up were 13 to 65 years of age, although they were excluded if they had a BMI >35 kg/m 2, had undergone prior extensive meniscectomy, or had ongoing progressive inflammatory arthritis. Patients were assessed clinically using the Knee Injury and Osteoarthritis Outcome Score (KOOS). Magnetic resonance imaging (MRI) was used to evaluate the graft using a 1.5-T or 3-T clinical scanner; the MRI assessment included 8 parameters of graft repair (infill, signal intensity, border integration, surface contour, structure, subchondral lamina, subchondral bone, and effusion) based on the magnetic resonance observation of cartilage repair tissue (MOCART) score as well as an MRI composite score. The degree of an association between the MRI parameters and the KOOS subscales at each postoperative time point was assessed with the Spearman correlation coefficient (SCC), and significance was determined at P < .05. Ethics approval was obtained from the appropriate hospital and university Human Research Ethics Committees, and informed consent was gathered from all patients. Results: The only MRI parameter displaying consistent evidence of an association with the KOOS subscales was effusion, with a pattern of increasing strength of correlations over time and statistically significant associations at 5 years with KOOS-Pain (SCC, 0.25; P = .020), KOOS–Activities of Daily Living (SCC, 0.26; P = .018), and KOOS-Sport (SCC, 0.32; P = .003). Apart from a significant correlation between subchondral lamina and KOOS-Sport at 1 year (SCC, 0.27; P = .016), no further significant findings were observed. Conclusion: Apart from some consistent evidence of an association between the KOOS and effusion, this analysis demonstrated a limited correlative capacity between clinical and radiological outcomes up to 5 years after surgery.